Gender and cross-country differences in the determinants of sustainable diet intentions: a multigroup analysis of the UK, China, Sweden, and Brazil - Chard, Emelie; Bergstad, Cecilia Jakobsson; Steentjes, Katharine; Poortinga, Wouter; Demski, Christina (Frontiers in Psychology, 2024)
Introduction Gender differences have been identified in both the engagement in and the determinants of sustainable diet behaviours. However, as engagement in pro-environmental behaviours varies across countries, the consistency of gender differences could follow similar patterns. Understanding the factors underlying gender and country differences in diet intentions is important for determining how to promote sustainable diets in different populations. Methods Using survey data from the UK, China, Sweden and Brazil (N=4,569), this paper examines the influence of subjective norms, diet-related identity, perceived status of meat consumption, environmental identity and environmental concern on sustainable diet intentions. Multigroup analysis was used to explore gender and country differences in the influence of these variables, and whether gender differences were consistent across the four countries. Results The findings show that there are gender differences in the influence of diet-related identity and perceived status of meat consumption, as well as cross-country differences in all factors except subjective norms. Holding a strong diet-related meat identity negatively affected sustainable diet intentions in all groups. Crucially, however, gender differences are not consistent across countries. Discussion These results suggest that individuals’ intentions to engage in sustainable diet behaviours are influenced by nationally unique gender associations.